Violencia intrafamiliar y su incidencia en el comportamiento de los estudiantes de la Unidad Educativa 24 de Mayo, año 2019 - Barco Hernandez, Teresa (2020)
Intra-family violence encompasses all behavior of physical, sexual or psychological violence that puts the security or welfare of a person in the family group in danger; the behavior of people who resort to both physical strength and emotional blackmail; the threats that give rise to the use of physical force, including sexual violence, both in the family and at home "Domestic Violence and its impact on the behavior of the students of the Educational Unit" May 24 " , year 2019. ”It is one of its most common forms and affects minors in particular. Child abuse prevents many of its victims from reaching their maximum educational level while deteriorating their physical and emotional health. When they reach adulthood However, little or nothing is done at the level of educational establishments, to know and remedy this problem, because the teacher has reduced his field of action only to the subject, to the development of a program, this It is, to instruction, forgetting its mission in the formation of future generations.